To Investigate the Effect of Targeted Overdilation in Balloon-Expandable Stents - Wong J (Dove Medical Press, 2021)
Jennifer Wong, Elliot Backer, Joseph C Keenan, Huseyin Erhan Dincer, Roy Joseph Cho Interventional Pulmonology Division, Department of Pulmonary, Allergy, Critical Care and Sleep Medicine, University of Minnesota, Minneapolis, MN, USACorrespondence: Roy Joseph Cho Tel +1 612-626-2637Email choxx548@umn.eduPurpose: Balloon-expandable stents are commonly used for the treatment of tracheobronchial strictures. We routinely perform targeted overdilation of these stents 1– 2mm on initial deployment to prevent stent migration or allow foreshortening to target airway caliber; however, specific data on the effect of targeted overdilation is unknown.Patients and Methods: We used three iCAST stents (6× 22mm, 7× 22mm, and 10× 38mm) to perform the study. We had two sets of each size to average our results. Targeted overdilation was accomplished with Merit Elation balloons.Results: The 6 × 22 and 7 × 22 stent OD increased from 6 to 11.4mm and 7 to 11.6mm. The 10 × 38 stent demonstrated minimal OD change with overdilation (OD change of 10.4 to 12.2mm). All stents demonstrated significant foreshortening with overdilation (20.2 to 5.65mm, 19.4 to 6mm, and 30.9 to 10.2mm for 6 × 22, 7 × 22, and 10 × 38, respectively). The breakpoint was seen at near twice the stated stent OD (13.5mm, 15mm, and 15mm with 6 × 22, 7 × 22 and 10 × 38, respectively).Conclusion: We have demonstrated that iCAST stents can increase their OD with subsequent foreshortening during targeted overdilation. This data can help facilitate decisions when selecting a particular iCAST stent for a specific airway application. Additionally, we have highlighted that balloon inflation diameter does not correspond to the actual stent OD during deployment. We believe that this data offers practical information for end-users of this stent type and additional data will be needed to corroborate our findings.Keywords: airway stenosis, tracheobronchial disease, interventional pulmonary, airway stent, balloon expandable stent, airway balloon dilation